The Impact of the Financial System Size on Sustainable Development - Kenig, Eduard; Secrieru, Angela (Acta Universitatis Danubius. Œconomica, 2025)
The present article delves into the relationship between the size of national financial systems and the level of countries’ sustainable development. The research’s relevance and importance are justified by the need to meet sustainability standards in society development and the crucial role of financial systems in the generative processes of sustainable development. The authors’ objectives were to establish the relationship between financial system size, measured through financial depth, and the sustainability level of national economies; measure the correlation between financial system depth and macroeconomic and financial parameters; and develop practical solutions to counter the negative impact of the financial system in the Republic of Moldova, which is characterized by insufficient financial depth, on national economy sustainability. The research process involved the application of system research methods and models, as well as analysis and synthesis, correlation analysis, factor analysis, dynamic analysis, and expert analysis. The article underscores the importance of financial integration at the regional level, the increase of foreign ownership of financial intermediaries, and the adaptation of regulations to the specifics of small financial systems, all of which have significant practical implications.